Sleep disturbance and cognition in the elderly: a narrative review - Ni, Yuanbo; Yu, Min; Liu, Cunming (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2024)
Sleep is an essential physiological process that promotes physical recovery and helps consolidate learning and memory. Common manifestations of sleep disturbances include insomnia, hypersomnia, circadian rhythm disorders, and parasomnias, all of which impair cognitive function, particularly in the elderly. Cognitive impairment is a significant factor that threatens the quality of life in the elderly, and there is currently no effective treatment for conditions such as dementia. The relationship between sleep and cognition is complex. Studies have shown that sleep disorders adversely affect cognitive function and increase the incidence of cognitive decline. This article focuses on sleep disturbances and their effects on the cognition of the elderly by reviewing research conducted over the past 20 years and describing potential mechanisms. Additionally, we explore the relationship between sleep and cognition during the perioperative period, aiming to identify strategies for optimizing perioperative sleep quality. We believe this review provides a deeper understanding of the association between sleep and cognition and offers a new perspective for perioperative management.